Crystal Structure of a Classical MHC Class I Molecule in Dogs; Comparison of DLA-88*0 and DLA-88*5 Category Molecules - Yujiao Sun; Lizhen Ma; Shen Li; Yawen Wang; Ruiqi Xiao; Junqi Yang; Johannes M. Dijkstra; Chun Xia (Cells, 2023)
DLA-88 is a classical major histocompatibility complex (MHC) class I gene in dogs, and allelic DLA-88 molecules have been divided into two categories named “DLA-88*0” and “DLA-88*5.” The defining difference between the two categories concerns an LQW motif in the α2 domain helical region of the DLA-88*5 molecules that includes the insertion of an extra amino acid compared to MHC class I consensus length. We here show that this motif has been exchanged by recombination between different DLA-88 evolutionary lineages. Previously, with pDLA-88*508:01, the structure of a molecule of the DLA-88*5 category was elucidated. The present study is the first to elucidate a structure, using X-ray crystallography, of the DLA-88*0 category, namely DLA-88*001:04 complexed with β2m and a nonamer peptide derived from canine distemper virus (CDV). The LQW motif that distinguishes DLA-88*5 from DLA-88*0 causes a shallower peptide binding groove (PBG) and a leucine exposed at the top of the α2 domain helix expected to affect T cell selection. Peptide ligand amino acid substitution and pMHC-I complex formation and stability analyses revealed that P2 and P3 are the major anchor residue positions for binding to DLA-88*001:04. We speculate that the distribution pattern of the LQW motif among canine classical MHC class I alleles represents a strategy to enhance allogeneic rejection by T cells of transmissible cancers such as canine transmissible venereal tumor (CTVT).